Postprandial effect of fresh and processed orange juice on the glucose metabolism, antioxidant activity and prospective food intake - de Paiva, Aline [UNESP]; Gonçalves, Danielle [UNESP]; Ferreira, Paula [UNESP]; Baldwin, Elizabeth; Cesar, Thais [UNESP] (Elsevier, 2019)
The impact of fresh squeezed orange juice (fresh OJ) and processed orange juice (processed OJ) on blood glucose and insulin was investigated. Prospective food intake and the short-term antioxidant effect were measured. Adult men and women (n = 36), lean and obese, were challenged on three different occasions with a dose of fresh OJ, processed OJ and a control drink (isocaloric sugar/acid-matched control orange-flavored drink). In lean individuals, the blood glucose was 11% lower after fresh OJ and 5% lower after processed OJ, whereas in obese individuals blood glucose fell 13% after 60 min of processed and fresh OJ compared to the control drink. Similarly, intake of both types of OJ decreased prospective food intake, but increased the antioxidant status of the blood. In conclusion, both types of OJ reduced blood glucose and short-term food intake, while increasing antioxidant status; however, lean subjects had better metabolic responses to OJ than obese subjects.
Keywords: Antioxidant status; Glucose; Insulin; Orange juice; Prospective food intake